Identification and Characterization of Myosin from Rat Testicular Peritubular Myoid Cells - Fernández, Dario (Society for the Study of Reproduction, Inc., 2008)
In the mammalian testis, peritubular myoid cells (PMCs) surround seminiferous tubules. These cells are contractile, express the cytoskeletal markers of true smooth muscle—alpha-isoactin and F-actin—and participate in the contraction of seminiferous tubules during the transport of spermatozoa and testicular fluid to the rete testis. Myosin from PMCs (PMC-myosin) was isolated from adult rat testis and purified by cycles of assembly-disassembly and sucrose gradient centrifugation. PMC-myosin was recognized by a monoclonal anti-smooth muscle myosin antibody, and the peptide sequence shared partial homology with rat smooth muscle myosin-II, MYH11 (also known as SMM-II). Most PMC-myosin (95%) was soluble in the PMC cytosol, and purified PMC-myosin did not assemble into filaments in the in vitro salt dialysis assay at 4°C, but did at 20°C. PMC-myosin filaments are stable to ionic strength to the same degree as gizzard MYH11 filaments, but PMC-myosin filaments were more unstable in the presence of ATP. When PMCs were induced to contract by endothelin 1, a fraction of the PMC-myosin was found to be involved in the contraction. From these results we infer that PMCs express an isoform of smooth muscle myosin-II that is characterized by solubility at physiological ionic strength, a requirement for high temperature to assemble into filaments in vitro, and instability at low ATP concentrations. PMC-myosin is part of the PMC contraction apparatus when PMCs are stimulated with endothelin 1.